1989
DOI: 10.2307/2937290
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Animal Processing of Detritus in a Woodland Stream

Abstract: The detritus standing crop, microbial respiration, and macroinvertebrate biomass were examined in monthly samples from the riffle sections of a first-order woodland stream. Total detritus was remarkably constant; the average (with 95% cL) ash-free dry mass standing crop was 426.4 ± 85.9 glm 2 over the 14 mo of the study. Throughout the year benthic detritus was dominated by fine particulate detritus ( < 1 mm), which made up 68.9% of the total ash-free dry mass. Woody debris made up 8%, whole leaves 3.5%, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 65 publications
1
60
1
1
Order By: Relevance
“…Some studies have demonstrated a consistent increase in microbial heterotrophic activity as detritus becomes smaller (Hargrave, 1972;Petersen et al, 1989). The nutritive value (e.g., organic matter content) of the sediment and the detritus may be an important predictor of microbial heterotrophic activity, as has been shown for bacteria (Findlay et al, 1986;Cole et al, 1988).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some studies have demonstrated a consistent increase in microbial heterotrophic activity as detritus becomes smaller (Hargrave, 1972;Petersen et al, 1989). The nutritive value (e.g., organic matter content) of the sediment and the detritus may be an important predictor of microbial heterotrophic activity, as has been shown for bacteria (Findlay et al, 1986;Cole et al, 1988).…”
Section: Introductionmentioning
confidence: 97%
“…The following fractions were considered: ultra-fine particles (< 70 µm), fine particles (70-300 µm), medium particles (300-1,000 µm) and coarse particles (> 1,000 µm). This size classification follows that proposed by Petersen et al (1989) for organic matter, with minor modifications. Petersen et al (1989) used the following classification: ultra-fine particles (0.5-75 µm), fine particles (75-250 µm), medium particles (250-1,000 µm) and coarse particles (> 1,000 µm).…”
Section: Sampling and Sediment Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1 mm sieve was used to separate BPOM into coarse BPOM (>I mm, BCPOM) and fine BPOM ( 4 mm BFPOM), according to Petersen et al (1989). Samples were then dried at 60°C, weighed, ashed at 60O0C, and reweighed.…”
Section: Methodsmentioning
confidence: 99%
“…It is a source of biologically-fixed energy to stream food webs. Wood is more biologically stable (GULIS et al, 2004) and less seasonal (PETERSEN et al, 1989) than other kinds of detritus, and studies have demonstrated that wood can serve as a food source for some species of stream invertebrates ANDERSON, 1982, 1987;BON-DAR et al, 2005). However, few studies have looked at the nutritional significance of small woody debris in stream ecosystems, whereas the predominant focus has been on leaves as a food resource in these systems (e.g., RICHARDSON, 1991RICHARDSON, , 1992WALLACE et al, 1999).…”
Section: Introductionmentioning
confidence: 99%